Gender biases in the Spanish financial and tax system. Proposals of solution - Díaz Calvarro, Julia María (2019)
The Spanish financial system, both in its budgetary and its tax structure, as well as in the measures described as ‘positive action’, has gender biases that perpetuate the role of women in the field of care, entailing opportunity costs in the development of their professional and personal life. The analysis of some of the most paradigmatic examples and the proposal of various solutions based on the feminist economy and gender taxation are the subject matter of this paper.